Short‐term external ureter stenting shows significant benefit in comparison to routine double‐J stent placement after ureterorenoscopic stone extraction: A prospective randomized trial – the Fast track stent study (FaST). (7th June 2018) - Bach, Peter; Reicherz, Alina; Teichman, Joel; Dahlkamp, Lisa; von Landenberg, Nicolas; Palisaar, Rein‐Jueri; Noldus, Joachim; von Bodman, Christian
Abstract : Objectives: To determine whether short‐term stenting using an external ureter catheter following ureterorenoscopic stone extraction provides a better outcome in comparison to double‐J stent ureteral stenting. Methods: Between August 2014 and August 2015, 141 patients initially managed with a double‐J stent insertion were prospectively randomized to ureter catheter for 6 h vs double‐J stent insertion for 5 days after stone extraction via ureteroscopy retrograde surgery (including flexible ureteroscopy retrograde surgery) in a single academic center. Endoscopic procedures were performed by nine surgeons. Exclusion criteria were acute urinary tract infection, a solitary kidney, or a stone mass more than 25 mm. Study endpoints were ureter‐stent related symptoms and pain assessed by a validated questionnaire (ureteral stent symptom questionnaire) and visual analogue scale before and 4 weeks after surgery. Results: Overall stone‐free rate was more than 90%. Mean operative time was 24 min (range 5–63). Groups did not differ in terms of age, body mass index, and stone size. Patients who received short‐term ureter catheter showed a significantly higher quality of life. In the ureter catheter group, the urinary index score (16.8 vs 27.8; P < 0.0001), the pain score (9.7 ± 1.3 vs 20.2 ± 1.5; P < 0.0001), and general health index (15.3 ± 0.7 vs 8.5 ± 0.6; P < 0.0001) were significantly lower. Consultation of a physician and antibiotic treatment were rarely needed (1.3 ± 0.1 vs 1.6 ± 0.1; P = 0.017). Conclusion: A short‐term ureter catheter insertion for 6 h following ureteroscopy retrograde surgery stone removal is a safe procedure and superior to double‐J stent insertion with regard to urinary symptoms, pain, quality of life, and stent related symptoms. Patients treated with a short‐term ureter catheter recover more quickly, return to work earlier, and need less doctor visits. Most patients would recommend a ureter catheter, and would prefer this strategy in case of future stone treatments.